What to do during Bacillus Calmette–Guérin shortage? Valid strategies based on evidence. Issue 6 (November 2018) - Abufaraj, Mohammad; Mostafid, Hugh; Shariat, Shahrokh F.; Babjuk, Marek
Abstract : Purpose of review: Over the last decade, the world has experienced health-threatening supply shortages of Bacillus Calmette–Guérin (BCG) immunotherapy for nonmuscle-invasive bladder cancer (NMIBC). We summarize the current literature to assist in treatment decisions in light of suboptimal supply. Recent findings: Currently available data do not support a superiority of one BCG strain over the other. Intravesical chemotherapy seems to provide similar results in term of disease progression but not recurrence in intermediate-risk patients. One trial has shown that a 3-year maintenance course of BCG in high-risk NMIBC has no advantage in term of progression or overall survival in comparison with 1-year maintenance. Synergo radiofrequency-induced hyperthermia is a reliable alternative in intermediate or high-risk NMIBC with at least similar recurrence rates compared with BCG. Summary: Patients with intermediate-risk NMIBC can be offered multiple instillations of intravesical chemotherapy for up to 12 months. In high-risk patients and in case of BCG shortage, BCG instillations can be terminated when the patient has completed 1 year of maintenance. Mitomycin C is an alternative in lowest risk high-risk (G3Ta) NMIBC, whereas patients with pT1/carcinoma in situ can be offered Synergo with mitomycin C when radical cystectomy is not feasible. Immediate radical cystectomy should always be considered in highest risk NMIBC after weighing up benefit to risk.